Tourism and Development: A Perspective Through Public Private Partnership - Sharma, Sunil (Socio-Economic Development Panorama, 2008)
In recent years tourism has become one of the fastest growing sectors of the world economy and is widely recognized for its contribution to regional and national economic development. In a diverse and fragmented tourism industry, there has arisen a need for partnerships to achieve broad-based support for policies within the industry. Partnerships in tourism development are a recent phenomenon. The paper contends that Public-Private Partnerships (PPPs) is an essential approach to tourism development, developing countries in particular. The PPPs approach is being used increasingly in developing countries and has emerged as a means to overcome the recognized fragmentation nature of tourism development. It has become clear to governments, tourism managers, planners and academics that no one individual organization can be effectively responsible for the development of tourism. There is a recognized need for coordination and cooperation within the public sector, and between the public and private sectors. This holds true for Nepal as well. Socio-Economic Development Panorama Vol.1(1) 2007 pp.113-124